Cloze testing for comprehension assessment: The HyTeC-cloze. (October 2019) - Kleijn, Suzanne; Pander Maat, Henk; Sanders, Ted
Although there are many methods available for assessing text comprehension, the cloze test is not widely acknowledged as one of them. Critiques on cloze testing center on its supposedly limited ability to measure comprehension beyond the sentence. However, these critiques do not hold for all types of cloze tests; the particular configuration of a cloze determines its validity. We review various cloze configurations and discuss their strengths and weaknesses. We propose a new cloze procedure specifically designed to gauge text comprehension: the Hybrid Text Comprehension cloze (HyTeC-cloze). It employs a hybrid mechanical-rational deletion strategy and semantic scoring of answers. The procedure was tested in a large-scale study, involving 2926 Dutch secondary school students with 120 unique cloze tests. Our results show that, in terms of reliability and validity, the HyTeC-cloze matches and sometimes outperforms standardized tests of reading ability.